Urbanization alters the spatiotemporal dynamics of plant–pollinator networks in a tropical megacity - Gabriel Marcacci; Catrin Westphal; Vikas S. Rao; Shabarish Kumar S.; K. B. Tharini; Vasuki V. Belavadi; Nils Nölke; Teja Tscharntke; Ingo Grass (Ecology Letters, 2023)
Urbanization is a major driver of biodiversity change but how it interacts with spatial and temporal gradients to influence the dynamics of plant–pollinator networks is poorly understood, especially in tropical urbanization hotspots. Here, we analysed the drivers of environmental, spatial and temporal turnover of plant–pollinator interactions (interaction β ‐diversity) along an urbanization gradient in Bengaluru, a South Indian megacity. The compositional turnover of plant–pollinator interactions differed more between seasons and with local urbanization intensity than with spatial distance, suggesting that seasonality and environmental filtering were more important than dispersal limitation for explaining plant–pollinator interaction β ‐diversity. Furthermore, urbanization amplified the seasonal dynamics of plant–pollinator interactions, with stronger temporal turnover in urban compared to rural sites, driven by greater turnover of native non‐crop plant species (not managed by people). Our study demonstrates that environmental, spatial and temporal gradients interact to shape the dynamics of plant–pollinator networks and urbanization can strongly amplify these dynamics.